PENYULUHAN TENTANG PENGELOLAAN SAMPAH 3R (REDUCE, REUSE, RECYCLE) DI KELURAHAN SEI LAIS KOTA PALEMBANG - Hestirinaih, Deby Chintia; Asteriniah, Femi; Herfriady, Herfriady (Aktivasi: Jurnal Pemberdayaan Masyarakat, 2023)
Community service in its implementation cannot be separated from the two other parts, namely Education and Teaching and Research. This community service was motivated by activities in Sei Lais Village, Kalidoni District, Palembang City. After conducting a survey in Sei Lais Village, Kalidoni District, RT 12 and RT 13 identified problems regarding waste management. Therefore, it is necessary to find a solution to reduce the amount of waste piled up. The right way is to run a waste management program with the "3R" pattern (reduce, reuse, recycle) in Sei Lais Village, Kalidoni District, Palembang City. The aim of this outreach is to provide additional information, increase public knowledge, and mobilize the behavior of the Sei Lais Village community to carry out waste management using the "3R" pattern in their respective homes. The method used is a coordination and implementation education at the activity location with several examples of items resulting from waste management using the "3R" pattern. The outreach activities went according to expectations, because they were supported by the seriousness of sub-district officials who encouraged their residents to take part in these outreach activities, the community was aware of the importance of the information provided, the community was interested in waste management using the "3R" pattern. The results of the outreach that had been carried out concluded that the community in Sei Lais Village did not yet know about "3R" waste management, because there had never been any education about this matter. Therefore, the community is very enthusiastic about the outreach material presented and will apply it at home.